Kesadaran, Sanksi Perpajakan, Kualitas Pelayanan Pajak, dan Kepatuhan Wajib Pajak Kendaraan Bermotor - Manuaba, I Gede Bagus Dony; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 33 No 9 (2023), 2023)
Motor Vehicle Tax contributes to Regional Original Income. The aim of this research is to determine the influence of Taxpayer awareness, tax sanctions, and service quality on Taxpayer compliance in paying Motor Vehicle Tax in Badung Regency. The sample used was 100 motor vehicle taxpayers using a non-probability sampling method, namely purposive sampling. The data analysis technique used is multiple linear regression using the SPSS version 26 program. The results of this research show that Taxpayer awareness, tax sanctions, and service quality have a positive influence on Taxpayer compliance in paying Motor Vehicle Tax at the SAMSAT Badung Joint Office. The theoretical implications of this research are able to provide additional information regarding taxpayer awareness, tax sanctions, and the quality of tax services and their influence on motor vehicle taxpayer compliance. Keywords: Motorized Vehicle Taxpayer Compliance; Taxpayer Awareness; Tax Sanctions; Quality of Tax Services